2015
DOI: 10.1002/2014ja020609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two large solar energetic particle events on middle atmosphere nighttime odd hydrogen and ozone content: Aura/MLS and TIMED/SABER measurements

Abstract: It is well established that large solar energetic particle (SEP) events affect ozone in the middle atmosphere through chemical reactions involving odd hydrogen (HO x ) species. We analyze global middle atmospheric effects at local nighttime for two large SEP events during the intervals of 7-17 November 2004 and 20-30 August 2005. Properties of the SEP events and concomitant geomagnetic storms are discussed using in situ measurements. Temporal dynamics and latitudinal distribution of HO x and ozone densities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Ozone has a secondary peak in the mesospheric altitude and it significantly affects sodium concentration. The atmospheric ozone concentration undergoes depletion during solar proton event (SPE) as well established from modeling and observations [ Jackman et al , , , , , ; Seppälä et al , ; Degenstein et al , ; Rohen et al , ; Verronen et al , ; Krivolutsky et al , ; Friederich et al , ; Verkhoglyadova et al , , and references therein]. Krivolutsky et al [] and Jackman et al [] reported depletion in ozone concentration during SEPs in 23rd solar cycle using models.…”
Section: Introductionmentioning
confidence: 93%
“…Ozone has a secondary peak in the mesospheric altitude and it significantly affects sodium concentration. The atmospheric ozone concentration undergoes depletion during solar proton event (SPE) as well established from modeling and observations [ Jackman et al , , , , , ; Seppälä et al , ; Degenstein et al , ; Rohen et al , ; Verronen et al , ; Krivolutsky et al , ; Friederich et al , ; Verkhoglyadova et al , , and references therein]. Krivolutsky et al [] and Jackman et al [] reported depletion in ozone concentration during SEPs in 23rd solar cycle using models.…”
Section: Introductionmentioning
confidence: 93%
“…The high reactivity makes the hydrogen radical of particular importance in atmospheric chemistry. During the SPEs, the increases in mesospheric OH have been observed (Damiani et al, ; Jackman et al, ; Verkhoglyadova et al, , ; Verronen et al, ). Jackman et al () compared the observations and model predictions and showed a good simulation of hydrogen radical and ozone during large SPEs.…”
Section: Introductionmentioning
confidence: 97%
“…Few of them explored the general influence on the atmospheric compositions and of the SPEs during the solar cycle 24 and the correlation between variations of the neutral components after the SPEs. Verkhoglyadova et al, 2015Verkhoglyadova et al, , 2016Verronen et al, 2006). Jackman et al (2014) compared the observations and model predictions and showed a good simulation of hydrogen radical and ozone during large SPEs.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous paper [ Verkhoglyadova et al ., , hereafter Paper I] we reported observations of changes in nighttime hydroxyl and ozone during two SEP events of 7–17 November 2004 and 20–30 August 2005 based on global measurements by two satellites. We showed a correspondence between the energetic proton flux (>10 MeV) measured at the Earth's orbit and the nighttime zonal average OH partial column density enhancements between 0.005 and 0.1 hPa (approximately from 65 km to 85 km in altitude).…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism is through ionization by precipitating high-energy particles, e.g., protons with~5 MeV deposit their maximum energy at~75 km altitude, which leads to an efficient ionization of atmosphere at this altitude [Turunen et al, 2009;Wissing and Kallenrode, 2009]. Among other effects, SEPs create odd hydrogen (HO x , primarily hydroxyl OH and HO 2 ) species through ion chemistry and cause ozone (O 3 ) destruction in the mesosphere [Solomon et al, 1981[Solomon et al, , 1983Jackman et al, 2005Jackman et al, , 2006Jackman et al, , 2011Verronen et al, 2006Verronen et al, , 2007Damiani et al, 2008Damiani et al, , 2010Verkhoglyadova et al, 2015]. For example, tertiary ozone maximum observed in wintertime high-latitude mesosphere around that altitude range [Marsh et al, 2001] is strongly affected by SEPs [Seppälä et al, 2006;Sofieva et al, 2009].…”
Section: Introductionmentioning
confidence: 99%